1997
DOI: 10.1016/s0167-2789(96)00167-4
|View full text |Cite
|
Sign up to set email alerts
|

Resonant interactions in Bénard-Marangoni convection in cylindrical containers

Abstract: Convection in a cylindrical container of small aspect ratio is studied. It is known that when, in addition to buoyancy forces, thermocapillarity effects are taken into account, resonant interactions of two modes may appear. In the case of 1:2 resonance amplitude equations are derived, showing the existence of a stable heteroclinic orbit and rotating waves, until now not observed experimentally.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This bifurcation arises in a variety of applications, including Rayleigh-Bénard convection in a plane layer [6,17], Marangoni convection in a cylindrical container [9], cellular flame patterns on a circular porous plug burner [15], turbulent boundary layer breakdown [8], and the von Kármán flow between two exactly counter-rotating disks [18]. In each of these cases imperfections may be present that break the assumed O(2) symmetry, i.e., the symmetry generated by rotations and reflection of a circle, or translations and reflections along the real line, modulo an imposed spatial period.…”
Section: Resultsmentioning
confidence: 99%
“…This bifurcation arises in a variety of applications, including Rayleigh-Bénard convection in a plane layer [6,17], Marangoni convection in a cylindrical container [9], cellular flame patterns on a circular porous plug burner [15], turbulent boundary layer breakdown [8], and the von Kármán flow between two exactly counter-rotating disks [18]. In each of these cases imperfections may be present that break the assumed O(2) symmetry, i.e., the symmetry generated by rotations and reflection of a circle, or translations and reflections along the real line, modulo an imposed spatial period.…”
Section: Resultsmentioning
confidence: 99%
“…This relation between Rayleigh and Marangoni number has been addressed in a previous work. 23 On the other hand, we do not vary R freely since we are interested only in the values it takes for our particular physical situation, therefore it is determined by ⌬T. These parameters are equivalent to the set of physical ones, d, ⌬T, l, ␦T c , and h. In this work we use any of these sets to define the physical state.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…Proctor and Jones [1988] analyzed a two-layer system using the normal form (4), locating parameter regimes with structurally stable heteroclinic cycles, but did not study the dynamics in the original pdes. Perhaps the best system for further study of the dynamical behavior studied here is provided by the Bénard-Marangoni problem in a cylinder [Echebarría et al, 1997] where heteroclinic cycles were also identified. Simulations of the relevant pdes as well as further experiments on this system are therefore of great interest.…”
Section: Discussionmentioning
confidence: 99%